The Creation of A Model of Development of Sports Management in Improving the Physical Training and Sports Management System in Uzbekistan - Komil Shamsievich, Ziyadullaev; Dilfuzakhon Ibrohimovna, Usmanova; Mirziyod Normurodovich, Mamatov; Rustam Yuldashevich, Babajanov; Umar Kobilovich, Alkorov (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the application of advanced methods and standards of physical education and sports management. Based on the goals and objectives of the research, it reflects the model of development of sports management in Uzbekistan in the field of physical culture and sports as an integrated system, the optimal management decisions in physical culture and sports organizations, and the content of strategic management models.